Sex hormones, metabolic status, and obesity in female patients with acne vulgaris along with clinical correlation: An observational cross-sectional study - Rumi Gayen; Indrashis Podder; Indranil Chakraborty; Satyendra Nath Chowdhury (Wolters Kluwer Medknow Publications, 2021)
Background: Acne vulgaris is a common dermatological disorder. Several hormones are suspected to play a role in its etiopathogenesis. Aims and Objectives: The aim of this study was to analyze the role of sex-hormones, metabolic status, and obesity in acne vulgaris and correlate with its severity and symptom load. Materials and Methods: This cross-sectional observational study included 89 female patients with acne vulgaris and certain phenotypic markers such as prepubertal onset, late-onset, persistent course, hirsutism, acanthosis nigricans, acrochordons, premenstrual flare, and diminished response to isotretinoin; suggestive of an underlying hormonal pathology. All patients were subjected to physical examination to rule out obesity and metabolic syndrome along with serum biochemistry to detect sex hormones (testosterone, progesterone, estrogen), serum insulin and insulin resistance (HOMA-IR) and lipid profile. Results: Among 89 patients (mean age 21.3 ± 5.3 years), 34.8% presented with late-onset/persistent/pre-pubertal acne, 33.7% presented with premenstrual flare and 28.2% presented with hirsutism. Hormonal analysis revealed elevated testosterone and progesterone with low estrogen across all categories of patients. Testosterone was significantly elevated even in mild acne. Serum lipid profile was altered significantly only in hirsute females. In total, 36% and 20.2% patients presented with metabolic syndrome and obesity, respectively; however, neither was associated with severity of acne. Conclusion: Sex-hormones, serum lipids, metabolic status, and body mass index are altered in acne vulgaris. All acne patients with endocrine markers should be evaluated for sex-hormones irrespective of severity and symptom load, whereas hirsutism may be regarded as clinical marker of lipid abnormalities. Metabolic syndrome and obesity do not seem to be directly correlated with acne severity. Thus, anti-androgens may be considered as adjuvant therapy in these patients, not responding to conventional therapy.